2023
DOI: 10.5688/ajpe9001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Student Perceptions of Blended and Online Learning Courses in Pharmacoeconomics, Management, and Leadership

Abstract: Objective: Blended learning combines traditional face-to-face education with online instruction. This learner-centered approach has been shown to improve student engagement, critical thinking, and performance outcomes. The objective of this study was to assess and trend student pharmacist perceptions of blended and online learning used to teach pharmacy management, leadership, and economics within a Pharm.D. curriculum. Methods: Qualitative methods were employed using in-depth, semi-structured interviews. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Overall, however, only 25% of them would completely stop online education, while others would continue to use the opportunities offered by online education, either in full or in a hybrid method. Frederick et al [32] obtained the same result. It is clear from their studies that during both online and hybrid education, young people considered flexibility, autonomy and the diversity of curriculum as positives.…”
Section: Literature Reviewmentioning
confidence: 55%
See 1 more Smart Citation
“…Overall, however, only 25% of them would completely stop online education, while others would continue to use the opportunities offered by online education, either in full or in a hybrid method. Frederick et al [32] obtained the same result. It is clear from their studies that during both online and hybrid education, young people considered flexibility, autonomy and the diversity of curriculum as positives.…”
Section: Literature Reviewmentioning
confidence: 55%
“…The easier accessibility of learning materials was evaluated as a positive aspect, while Slovak students also prefer remote exams. The time and cost savings from the absence of travel, flexible schedules, and home comfort, which are mentioned in the literature as essential positives [4,24,25,28,[31][32][33][34], were not mentioned as decisive factors for the students surveyed in this study. Even though the digital generation's use of IT devices and the Internet has recently increased, regardless of the pandemic, university students still use the materials and literature provided or recommended by the lecturer and do not take the trouble to search and develop literature on the subject themselves.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Ahmed et al (2021) found that while some students showed interest in online learning, most preferred traditional FTF lectures [ 33 ]. On the other hand, a recent study by Frederick et al (2023) demonstrated that pharmacy students perceived blended learning positively for delivering a pharmacy course on management, leadership, and economics compared to FTF learning [ 34 ]. Bączek et al (2020) did not find a difference between medical students’ opinions toward FTF and online learning in terms of increasing knowledge [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blended learning has several advantages for both teachers and students. Teachers can facilitate students' independent learning [4], and they can also foster students' critical thinking in solving real world problems [5] Blended learning can also enhance students' engagement in the classroom through lively interactions [6,7]. In higher education, blended learning model not only improve students' knowledge and skills acquisition, but also saving educational cost [8,9].…”
Section: Innovative Blended Learning Modelmentioning
confidence: 99%